Effects of gut microbiota interventions on patients with schizophrenia: a systematic review and meta-analysis - Ye, Nianhua; Song, Xin; Yu, Jing; Bao, Xiaolei; Ye, Minghua; Jiang, Lisheng (Frontiers in Microbiology, 2025)
IntroductionSchizophrenia (SCH) is a chronic psychiatric disorder characterized by disturbances in thought, emotion, perception, and behavior. Although gut microbiota interventions (e.g., probiotics, prebiotics, synbiotics, dietary modifications and fecal microbiota transplantation) have been widely applied in the treatment of SCH, the most effective intervention strategy remains uncertain.MethodsBy searching four databases, only randomized controlled trials (RCTs) were included to examine the impacts of gut microbiota interventions on SCH. The Cochrane risk-of-bias tool for randomized trials (RoB 2.0) was employed to assess the methodological quality of the included studies, RevMan5.4 was used for the meta-analysis, Stata 18 was used for sensitivity analysis, Engauge Digitizer was used to convert pictures to numbers and GRADEPro3.6 was used to grade the evidence quality.ResultsThis study incorporated RCTs published from the earliest records up to December 2024. A total of 10 RCTs, encompassing 585 participants, were analyzed. The meta-analysis demonstrated that interventions primarily utilizing probiotics to modulate gut microbiota significantly lowered the total Positive and Negative Syndrome Scale (PANSS) scores among patients (p = 0.001). Furthermore, substantial improvements were observed across multiple metabolic parameters: fasting blood sugar, triglycerides, total cholesterol, homeostasis model assessment of insulin resistance, and quantitative insulin sensitivity check index (all p < 0.05). While no significant effects were observed on high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, body weight, body mass index, and insulin.ConclusionThis meta-analysis suggests that auxiliary probiotic interventions hold promise as an adjunctive therapy for schizophrenia, potentially yielding benefits in psychopathological, metabolic, and physiological domains. However, the current evidence remains inconclusive due to the limited number of studies, small sample sizes, and methodological variations. Firm therapeutic recommendations cannot be made at this time. The findings underscore the need for more robust, large-scale, and rigorously designed randomized controlled trials to definitively establish the efficacy and optimal protocols of auxiliary probiotic supplementation for SCH.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, CRD 420250652507.